Identification of multiple extracellular signal-regulated kinases (ERKs) with antipeptide antibodies. - Boulton, T G (1991)
A protein kinase characterized by its ability to phosphorylate microtubule-associated protein-2 (MAP2) and myelin basic protein (MBP) is thought to play a pivotal role in the transduction of signals from many receptors in response to their ligands. A kinase with such activity, named extracellular signal-regulated kinase 1 (ERK1), is activated rapidly by numerous extracellular signals, requires phosphorylation on tyrosine to be fully active, and in vitro can activate a kinase (a ribosomal S6 protein kinase) that is downstream in phosphorylation cascades. From the protein sequence predicted by the rat ERK1 cDNA, peptides were synthesized and used to elicit antibodies. The antibodies recognize both ERK1; a closely related kinase, ERK2; and a third novel ERK-related protein. Using these antibodies we have determined that ERK1 and ERK2 are ubiquitously distributed in rat tissues. Both enzymes are expressed most highly in brain and spinal cord as are their mRNAs. The third ERK protein was found in spinal cord and in testes. The antibodies detect ERKs in cell lines from multiple species, including human, mouse, dog, chicken, and frog, in addition to rat, indicating that the kinases are conserved across species. ERK1 and ERK2 have been separated by chromatography on Mono Q. Stimulation by insulin increases the phosphorylation of both kinases on tyrosine residues, as assessed by immunoblotting with phosphotyrosine antibodies, and retards their elution from Mono Q. Each of these ERKs appears to account for a distinct peak of MBP kinase activity. The activity in each peak is diminished by incubation with either phosphatase 2a or CD45. Therefore, both enzymes have similar modes of regulation and appear to contribute to the growth factor-stimulated MAP2/MBP kinase activity measured in cell extracts.